2000
DOI: 10.1093/ndt/15.4.498
|View full text |Cite
|
Sign up to set email alerts
|

Altered IgG4 renal clearance in patients with inflammatory bowel diseases. Evidence for a subclinical impairment of protein charge renal selectivity

Abstract: Renal protein charge permselectivity is impaired in 40% of patients with IBD with no overt proteinuria. Our data suggest that altered IgG(4) clearance may represent a subclinical marker of renal involvement in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In this study, expression of NHE isoforms was examined in the renal cortex in colitic animals. The present findings demonstrate a selective induction of NHE-3 in the renal cortex of colitic animals, supporting earlier reports showing involvement of kidneys under IBD conditions [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27]. However, lack of significant difference in the yield of renal crude microsomal proteins suggests that the induction of NHE-3 is not due to any overt change such as hyperplasia or hypertrophy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, expression of NHE isoforms was examined in the renal cortex in colitic animals. The present findings demonstrate a selective induction of NHE-3 in the renal cortex of colitic animals, supporting earlier reports showing involvement of kidneys under IBD conditions [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27]. However, lack of significant difference in the yield of renal crude microsomal proteins suggests that the induction of NHE-3 is not due to any overt change such as hyperplasia or hypertrophy.…”
Section: Discussionsupporting
confidence: 90%
“…Kidneys play an important role in maintaining the electrolyte and water homeostasis by having several ion-transporting systems [12, 13, 14, 15, 16], including NHE, however the role of renal cortical NHE remains to be established in colitis. In this context, changes in the renal structure and functions reported in inflammatory bowel disease (IBD) condition in humans are important [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27]. For example, necrosis, tubular damage, changes in the renal permeability, IgA nephropathy or increased chances of renal stone formation are some well-documented extraintestinal manifestations reported in IBD patients [17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed that glycation of protein increases its acidic nature [42]. At acidic pH, binding of protein to FcRn receptors is higher when compared to physiological pH [43].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors have been unable to establish a correlation between several urinary markers of renal damage and 5-ASA treatment. 40,84 Furthermore, Riley et al 9 found that the incidence of elevated urinary markers (such as ␤-N-acetyl-D-glucosamidase) is low in patients with quiescent UC, which is independent of the dose and duration of 5-ASA treatment.…”
Section: Renal Markers Of Nephrotoxicitymentioning
confidence: 99%